The Relation Between Supervisors’ Big Five Personality Traits and Employees’ Experiences of Abusive Supervision - Camps, Jeroen; Stouten, Jeroen; Euwema, Martin (Frontiers in Psychology, 2016)
The present study investigates the relation between supervisors’ personality traits and employees’ experiences of supervisory abuse, an area that – to date – remained largely unexplored in previous research. Field data collected from 103 supervisor-subordinate dyads showed that contrary to our expectations supervisors’ agreeableness and neuroticism were not significantly related to abusive supervision, nor were supervisors’ extraversion or openness to experience. Interestingly, however, our findings revealed a positive relation between supervisors’ conscientiousness and abusive supervision. That is, supervisors high in conscientiousness were more likely to be perceived as an abusive supervisor by their employees. Overall, our findings do suggest that supervisors’ Big Five personality traits explain only a limited amount of the variability in employees’ experiences of abusive supervision.